The convective description of kinematics of finite elasto-plastic deformations - Wojciech Dornowski (Biuletyn Wojskowej Akademii Technicznej, 2016)
The convective description of kinematics of finite elasto-plastic deformations is presented. From the numerical application point of view, such an approach is very useful [4]. It also leads to clear interpretation of the geometrical sense of tensor transformation. Transformation rules for the spatial tensor field objective at superposed spatial diffeomorphism are given. The local notion of the tangent space unloaded elastically is introduced. The metric tensor defined in this space is the purely plastic deformation measure. It is shown that transformation of this tensor to any other configuration leads to other deformation measures but ever plastic one. Within the limits of the concept of covariance it is shown that the additive decompositions, in which strains and their rates decompose additively into elastic and plastic parts, can be derived from the multiplicative decomposition of the deformation gradient. Using the free energy function, the formulation of material objectivity of the constitutive structure with a finite set of internal variables is proposed. Making use of this formulation, the general form of the rate type constitutive structure is presented.[b]Keywords[/b]: elasto-plasticity, large deformations